Perancangan Sistem Informasi Penilaian Angka Kredit Kenaikan Jabatan Fungsional Atau Pangkat Dosen di Fakultas Tarbiyah Dan Ilmu Keguruan UIN Bukittinggi - Ariza, Zulhadi (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
The background of this thesis research is the activity of calculating credit scores for promotion to functional positions or the rank of lecturers at the Faculty of Tarbiyah and Teacher Training (FTIK) UIN Bukittinggi which currently still uses a manual system, namely lecturers collect data sheet by sheet so that data will accumulate and be difficult to manage. . Therefore the authors designed an Information System for Assessment of Credit Scores for Increases in Functional Positions or Lecturer Ranks at the Tarbiyah and Teacher Training Faculty of UIN Bukittinggi to facilitate OKPP UIN Bukittinggi in assessing credit scores submitted by FTIK UIN Bukittinggi lecturers. The activity of assessing lecturer credit scores is intended for the benefit of proposing academic positions or lecturer ranks that require basic and comprehensive improvements. The purpose of this research is to assist lecturers in the process of submitting promotions and to facilitate OKPP UIN Bukittinggi in the process of calculating credit scores submitted by FTIK UIN Bukittinggi lecturers. The type of research used in this study is the ADDIE research and development (R&D) model, namely Analyze, Design, Develop, Implement, Evaluate. This study also uses an assessment test of validity, practicality, and effectiveness. The results of the validity test were carried out on three expert lecturers, namely three people in the field of technology. Based on this test, the system gets a value of 0.75 which means the resulting system is valid. The practicality test was carried out on two employees and promotion managers from OKPP UIN Bukittinggi, who obtained a practicality score of 80%, which means that the resulting system is practical. The final test was an effectiveness test conducted on 4 FTIK UIN Bukittinggi lecturers, with the final result being 0.91, which means that this system has high effectiveness.